Enhancing Mathematical Spatial Literacy through Project-Based Blended Learning with Cognitive Conflict Strategy - Rika Mulyati Mustika Sari; kiki Nia Sania Effendi; Indrie Noor Aini; Hanifah Nurus Sopiany; Nenden Suciyati Sartika; Annisaa Kossahdasabitah (Jurnal Pendidikan MIPA, 2026)
This article discusses the development of a project-based blended learning (PjBBL) module using a cognitive conflict strategy on the topic of geometric transformations to enhance mathematical spatial literacy. The objectives of this study are (1) to produce a valid, practical design of a PjBBL module with a cognitive conflict strategy, and (2) to determine the improvement in the mathematical spatial literacy of eleventh-grade senior high school students after implementing the module. This research is a design research using the Plomp model. The initial stage of the Plomp model, namely the preliminary research stage, is to identify the problems and needs required in learning. The second stage is prototyping, namely, compiling a prototype after obtaining the results of the initial investigation, followed by formative evaluation; the third stage is assessment. The data collection techniques and instruments used were interviews, observations, and mathematical spatial literacy tests. The results of the module development were evaluated based on three aspects, namely validity, practicality, and effectiveness, involving students from SMAN 1 Cicalengka as the research subjects. The research data were analyzed descriptively. The results showed that the design of the project-based learning teaching module using the cognitive conflict strategy was in the very valid category, with an obtained score of 84. Valid based on material and media experts from the results of the feasibility of content, presentation, language, contextual, and graphics (module size, cover design, and module content design). For the practicality value, a result of 86.3, including the very practical category, was obtained based on the results of the practicality test of student responses to the criteria of presentation, language, content, and time. The effectiveness of the module is evidenced by an increase in students' mathematical spatial literacy, with high N-gain and a large effect size. Keywords: project-based learning, cognitive conflict strategy, mathematical spatial literacy.